Enhancement of tunnel magnetoresistance in fully perpendicular MnGa-based magnetic tunnel junctions with metastable bcc CoMnFe interlayer - Deepak Kumar; Naoki Kamata; Kwon Hyeokjin; Shigemi Mizukami (AIP Advances)
We investigated the tunnel magnetoresistance (TMR) effect in fully perpendicular magnetized MnGa-based magnetic tunnel junctions (MTJs) with CoFeB as the top electrode. In these perpendicular (p)-MTJs, thin metastable body-centered cubic (bcc) CoMnFe alloys are used as an interlayer between the MgO barrier and MnGa layers to enhance the TMR ratio. This study highlights the utility of bcc Co-based alloys, such as CoMnFe, which exhibit antiferromagnetic coupling with MnGa in p-MTJs. The TMR ratios of ∼106% and 110% were observed corresponding to single and double interface p-MTJs, respectively, after annealing at 300 °C, demonstrating the potential of these materials for high-performance spin-transfer torque (STT) devices based on p-MTJs.